Penggunaan Media Konkret Dalam Pembelajaran IPA Untuk Meningkatkan Pemahaman Materi Pada Siswa Kelas III SD - Selviana Tantri Imani; Raihan Gymnastiar; Fitri Saswani (LPPM Sekolah Tinggi Ilmu Tarbiyah Muhammadiyah Bojonegoro, 2025)
Science learning (IPA) in elementary schools requires active student involvement so that the concepts learned can be understood meaningfully. Third-grade elementary school students are at the concrete operational stage, therefore they need learning media that are concrete in nature. This study aims to describe the use of concrete media in science learning and its impact on students’ understanding of learning materials in grade III of elementary school. The research method used was qualitative with a descriptive approach. The research subjects consisted of a third-grade teacher and students of SDN Bangsekol 1. Data collection techniques included observation, interviews, and analysis of student worksheets (LKPD). The results showed that the use of concrete media such as animal models and live plants was able to increase students’ activeness, motivation, and understanding of the concepts of life cycles and animal body parts. Students were able to remember and explain the learning material more easily because they were directly involved in the learning process. Thus, concrete media proved to be effective for use in science learning for third-grade elementary school students.